Stakeholders and information technology in education : IFIP TC 3 International Conference, SaITE 2016, Guimarães, Portugal, July 5-8, 2016, Revised selected papers /: IFIP TC 3 International Conference, SaITE 2016, Guimarães, Portugal, July 5-8, 2016, Revised selected papers. (2016) - Unknown
No abstract available